Definition of biomechanical parameters of technical actions in the martial arts - V.S. Muntian (Physical Education of Students, 2013)
Questions of efficiency of training process and competitive activities are considered. The possibilities of accounting in preparing the athletes of the laws of biomechanics and anthropometric characteristics of individual athletes. The experiment involved 16 qualified athletes (age 19-25 years) engaged in hand to hand combat. Revealed that body movement back and forth (back slope protection and application of direct counterattacking punch) should be regarded as rotational propulsion. It is shown that the length and mass of the parts of the body affect the moment of inertia. Emphasized that in order to determine the level of technical and tactical skills of athletes should conduct research in the field. The effect of the height-weight indices, the length and mass of parts of the body at the moment of inertia. Established their influence on the speed of the predominantly translational and rotational movements, the timing and energy performance of technical activities.